Modelo Pedagogico de Educacion Primaria para Adultos Manual para el Asesor de Estudiantes Libres. Primera Parte. - Instituto Nacional para la Educacion de los Adultos, Mexico City (Mexico).; Instituto Nacional para la Educacion de los Adultos, Mexico City (Mexico). ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1990)
This guide, part of a Mexican series of instructional materials, is intended for advisors of students participating in an adult education program offered through public and private organizations in communities in Mexico. The first part of the program comprises Spanish and math; the second, education for family life, education for community life, education for work life, and education for citizenship. The program is designed for both the recently literate and those with some schooling. The general objective of the first part of the curriculum is to teach students to express themselves with confidence, both orally and in writing. Advisors identify areas of study in which the student needs assistance. The advisor specifies the units to be reviewed and plans the time the student will dedicate to each unit. The advisor explains the general and area objectives, the sequence and program of study, the purpose of the activities planned for monthly meetings and home visits, and the accreditation system. In the second part of the curriculum, students review previous lessons, are introduced to new topics, and invited to reflect on the importance of the topics to their daily life. The advisor points out what has been learned and remarks on its usefulness, planning with the students the activities they will perform until the following group or individual meeting and recommending study techniques and extra exercises for the students who have had more difficulties. (Adjunct ERIC Clearinghouse for ESL Literacy Education) (IC)
ERIC Note: For related documents, see FL 801 047-068. Photographs may not copy well.
Teachers.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adult Basic Education; Adult Students; Community Education; Foreign Countries; Functional Literacy; Guidelines; Independent Study; Instructional Materials; Learning Strategies; Models; Orientation Materials; Spanish Speaking; Textbook Content; Mexico; Guides, Classroom -- Teacher